GIANT POROCARCINOMA OF THE LEG - DIAGNOSTIC AND THEARPEUTIC CHALENGES, AND POSSIBLE INFLUENCE OF THE COVID-19 PANDEMIC ON THE DIAGNOSIS AND TREATMENT - Jeremic, Prof. Jelena (Medical Research, 2024)
Introduction: Cutaneous porocarcinoma represents a rare, malignant tumor, arising from the eccrine sweat gland. High rates of extracutaneous spread, local reccurence and high mortality are observed. Definitive diagnosis could be complex due to its histopathological similarity to squamous cell skin carcinoma and Paget's disease. Primary treatment still relies on surgical excision. Patient review: A 76-year-old male presented at our clinic in January 2020, with a bleeding skin tumor of the right thigh. Multiple wide surgical excisions have been performed between January 2020 and November 2022, due to repetitive local recurrence. For a period of time, our patient was lost to follow up caused by COVID-19 pneumonia and long recovery period. Initially, a poorly differentiated squamous cell skin carcinoma was reported. Following specimens reported porocarcinoma. On follow-ups, apart from skin tumor recurrence, inguinal nodal involvement was confirmed. CT showed no signs of disseminated disease in the lungs or in the abdomen, in any of the succeeding follow-ups. Finally, the MRI of the pelvis revealed a suspicious mass in the bladder, radiologically consistent with metastatic disease and was further referred to an oncologist and urologist. Conclusion: Porocarcinoma remains insufficiently explored. There are no official treatment protocols. Due to its similarity to squamous cell carcinoma dermatopathology expert should be consulted, while the management necessitates a multidisciplinary approach. Since early diagnosis and treatment are of paramount importance, factors delay those actions, as was with our case and the Covid-19 pandemic could be detrimental to a patient, and poorly affect prognosis and final outcome.
Keywords: eccrine porocarcinoma, porocarcinoma, skin tumors, COVID-19